Content Distribution Mecbanisms of Named Data Networking - Kai Lei; Jie Yuan (Dianxin kexue)
Future internet architecture research is one of the major strategic needs of science and technology development. As a promising design, named data networking（NDN）has drawn the extensive attentions of researchers and industry. Since NDN architecture evolves the internet from today's host-based packet delivery towards directly retrieving named objects, there are still a lot of issues have yet to be studied. Its content distribution mechanisms are the key to promote the development and deployment. The concepts and characteristics of NDN content distribution were introduced. The current advances in the aspect of forwarding strategy, redundant control, congestion control and access control were emphasized. Aimed at the faced problems, some discussions and analysis were also presented.